An Equal Match: Simultaneous vs. Sequential Methods in Face Testimony Accuracy: [Setara: Metode Simultaneous vs. Sequential Dalam Keakuratan Kesaksian Wajah] - Rahayu, Yusti Probowati; Hartoko, Kevin; Ajuni; Wirawan, Hillman (ANIMA Indonesian Psychological Journal, 2023)
The number of crimes in Indonesia has increased since 2014. In each crime, there are usually witnesses who testify. Witnesses are important in every process, starting from investigation, prosecution, and trial. There are two methods commonly used in the process of identifying facial testimony, namely the simultaneous method and the sequential method. This study is a quantitative experimental research study that aims to determine differences in the accuracy of testimonies using the simultaneous and sequential methods, with undergraduate students as participants. The results of the cross-tabulation of the accuracy of testimony using the simultaneous and sequential methods (p = .335; p > .05) showed that the accuracy of the testimony was not affected. Correlation tests were also performed on the accuracy of testimony and confidence using the biserial point correlation test. Correlation test results (r = .051; p > .05) show that eyewitness’ confidence is not related to the accuracy of testimony. Jumlah tindak kejahatan di Indonesia meningkat sejak tahun 2014. Pada tiap tindak kejahatan biasanya terdapat saksi yang memberikan kesaksian. Saksi adalah penting dalam setiap proses, mulai dari penyidikan, penuntutan, dan pengadilan. Terdapat dua metode yang umum digunakan saat proses identifikasi kesaksian wajah, yaitu metode simultaneous dan metode sequential. Studi ini merupakan studi penelitian kuantitatif eksperimen yang bertujuan untuk mengetahui perbedaan keakuratan kesaksian dengan metode simultaneous dan metode sequential, dengan partisipan mahasiswa dan mahasiswi program sarjana. Hasil tabulasi silang keakuratan kesaksian dengan metode simultaneous dan metode sequential (p = 0,335; p > 0,05) menunjukkan bahwa keakuratan kesaksian tidak dipengaruhi oleh kedua metode. Uji korelasi juga dilakukan terhadap keakuratan kesaksian dan keyakinan diri menggunakan uji korelasi poin biserial. Hasil uji korelasi (r = 0,051; p > 0,05) menunjukkan bahwa keyakinan diri saksi mata tidak terkait dengan keakuratan kesaksian.